Stocks as a Canvas: Enhancing Comprehension and Financial Analysis toward Intelligent Investment at SMAN 1 Moyo Utara - Muhammad Tezar Hairullah; Ari Miftahur; Dani Ardiansyah; Miranda Rosa Pratiwi; Arya Zufikar Akbar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
SMAN 1 Moyo Utara encounters difficulties associated with inadequate financial literacy, particularly concerning capital market investments. Despite the establishment of an Investment Education Gallery (GIE) in 2021, the facility remains underutilized due to the inadequate comprehension of investments among students and teachers.  This community service aims to: Enhance the understanding of students and educators at SMAN 1 Moyo Utara about investments through education and training in the capital market; Incorporate the IDX Mobile Application to facilitate direct practice, offering practical experience for students and educators at SMAN 1 Moyo Utara; Identify prospective students capable of becoming leaders of the investment education gallery at SMAN 1 Moyo Utara, ensuring the sustainability of educational and training initiatives. This program effectively enhanced participants' comprehension, as evidenced by pre- and post-tests, as well as their capacity for autonomous trading.  The trading competition offered a pragmatic venue for students, and its outcomes facilitated the identification of prospective students to oversee the school's investment gallery. Strategies for ongoing education and the use of social media to enhance educational outreach bolster the program's viability.